Exegesis Translation of the Qur’an Containing Sanat-e-Atala "Dars e Kalam Ullah", a Review - Hina Tosief; Dr. Sadaf Naqvi (Zaban-o-Adab, 2023)
’’Dars e Kalam Ullah". It is the first Sanat-e-Atala exegetical translation of the Qur’an in the Urdu language, which is done by Dr. Tahir Mustafa. Before this, the exegesis of the Holy Qur’an has been written in Sanat-e-Atala, but they are primarily in Arabic language or are done partially. Dr. Tahir Mustafa has the honor of making the first and only ghair manqoot exegetical translation of the Qur’an in Urdu language so far. He has made a complete exegetical translation of the Holy Qur’an by staying confined to the circle of 18 ghair manqoot letters out of the 37 letters of Urdu. Its first edition was published in April 2021 and received great acclaim in various academic, literary and religious circles. Its second edition was published in May 2022. "Dars e Kalam Ullah" consists of 1421 pages, 98% of which has been written in Urdu, and 2% of words from other languages. This special relationship of Dr. Sahib with a great and holy book like the Holy Quran is undoubtedly a gift from God which is a characteristic of fortunate people. Quran experts have called this translation a new and beautiful addition to the literature of Quranic studies.